Impacto técnico y financiero de la resolución CREG. 038 del 2014 para un comercializador de energía en Colombia - Duran Fetecua, Erika Alejandra (Universidad Antonio Nariño, 2021)
In Colombia, pursuant to the provisions of Law 142 of 1994, some users of electrical energy can freely choose the energy service provider. The commercialization activity is defined as the purchase of energy in the wholesale market and sale to other agents or end users. The commercialization activity is carried out jointly with the distribution activity, for this reason, in parallel, the legislation creates regulations to give guarantees in energy measurement, creating a measurement code which is born as an annex (Sheet 133) of CREG Resolution 025 of 1995 (Networks Code), reaching its last update under CREG Resolution 038 of 2014. The latter establishes all the characteristics, conditions, requirements, operation and maintenance that an energy measurement system must meet, as well as defines, among others things, the normalization times of a commercial border and the procedures for collecting, storing and reporting energy consumption to the Administrator of the Commercial Exchange System-ASIC. In the present project, the technical and financial impact generated from the entry into force of CREG Resolution 038 of 2014 will be analyzed in the first instance to the marketer who is the one who, before the ASIC, must directly face the guarantee that the code is Complies, in this case for practical purposes an Energy Trading Company will be taken and in the second instance the impact generated to the end user. The different phases of the process will provide evidence of the action plans that were taken to be able to strictly comply with the regulations and with the latter, an attempt will be made to break down the repercussions generated in the process of audits carried out to verify compliance with the regulations.